Species Diversity of Birds at Padawan Limestone Area, Sarawak. - Mohammad Saiful, Mansor (Universiti Malaysia Sarawak, (UNIMAS), 2009)
study of species diversity of birds was conducted in Padawan limestone area, Sarawak for six days at Kg. Giam and five days at Danu. The purpose of the study was to compare the species richness and relative abundance between Padawan limestone and other limestone areas as well as the other type of forests. In addition, the species abundance of undisturbed and disturbed areas in both study sites was investigated. Twenty mist-nets were deployed for 12 hours daily and incidental observation was conducted during the study period. A total of 80 species from 34 families were recorded at both sites. At Kg. Giam, 120 birds were mist-netted representing 31 species from 16 families while 13 species from 11 families were recorded by observation. In the undisturbed area, 21 species from 13 families were mist-netted. In disturbed area, 21 species from 10 families were mist-netted. At Danu, a total of 48 birds were mist-netted representing 25 species from 12 families while 34 species from 19 families were recorded by observation. In the undisturbed area, 12 species from seven families were mist-netted. In disturbed area, 18 species from 11 families were mist-netted. The statistical analyses showed that there was significant difference in species diversity index between undisturbed and disturbed areas. The overall capture rate for this study was 64 birds per 1,000 nethours.